Skutki podatkowe odpisów aktualizujących wartość należności - Bogacz-Miętka, Olga (Fiscal Results of Making Reserves for Bad Debt, 2005)
In accordance with the Polish income tax legislation, reserves for had debt are not considered as the tax costs. However the Income Tax Law specifies the exceptions to this rule. After meeting the legal conditions reserves for bad debt it can be rated among the tax costs. This article presents fiscal results connected with making reserves for bad debt and with ceasing of the reason for which reserves for bad debt were made. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 208-218